Identity, Empathy and Argument: Immigrants in Culture and Entertainment Journalism in the Scandinavian Press - Riegert, Kristina; Hovden, Jan Fredrik (Javnost-The Public, 2019)
Cultural and entertainment journalism deals with aesthetic experiences, advice on cultural consumption, as well as reflection and debate on ethical and moral humanistic issues. Does this sub-field of journalism systematically represent immigrants and integration differently than the other news and commentary articles? Comparing immigration discourse in a representative sample of six Scandinavian newspapers between 1970 and 2016 using content analysis we find that cultural journalism, while clearly reverbing with the dominant national issues at the time, did provide alternative perspectives. It not only brought up themes like racism, multiculturalism, national identity and religion more often, but was also more positive, more gender-balanced and more often gave a voice to immigrants than other news did. A closer qualitative reading further suggests a typology of ten main story-types, varying relatively little over time and across national borders. Cultural journalism in this case illustrates how the cultural public sphere can positively contribute to the debate of complicated issues in the public sphere by offering resources for identification, empathy and arguments for specific points of view.